Evaluation of noise exposure levels of pedestrians in suburban Chennai, India - Salim, Minu; Saravanan, Suriya (Journal of Environmental Engineering and Landscape Management, 2024)
The study assessed traffic noise exposure levels of citizens walking on the sidewalks at important road crossings in commercial land zone regions of Chennai’s suburbs. The noise data from signalized and unsignalized intersections are collected with a class I sound level meter for peak and non-peak hours from 6 AM to 10 PM. Different noise indices like A-weighted equivalent continuous noise level (Leq), Traffic Noise Index (TNI), Noise Pollution Level (Lnp) and Noise Climate (NC) are calculated and compared with Central Pollution Control Board (CPCB, 2017) and WHO standards. The inhabitants’ noise exposure levels are at an average value of 80–107.1 dB(A) which is alarmingly higher than the threshold levels of 70 dB(A) by WHO. A Risk Exposure Assessment (REA) questionnaire survey conducted on the area revealed that unsafe health situations persist for the public in the study regions.